When do retailers benefit from special ordering?. Issue 2 (8th February 2010) - Gupta, Diwakar; Gurnani, Haresh; Chen, Hao-Wei
Many retailers offer to special order out-of-stock items at no additional cost to the customers. This practice is based on an implicit assumption that by increasing sales and reducing stockouts, special orders increase retailers' profits. We study the relative benefit of special ordering to the retailer and show that this assumption may not hold. Our model reveals two counter-intuitive results. First, the retailer's expected profit is higher when the manufacturer has additional pricing flexibility, i.e., the manufacturer offers two prices, a base price for the primary order and a different price for the special order, as compared to a single price for all items. Second, higher demand variability may increase retailer's profits.